2010
DOI: 10.1542/peds.2009-0539
|View full text |Cite
|
Sign up to set email alerts
|

The “Cough Trick:” A Brief Strategy to Manage Pediatric Pain From Immunization Injections

Abstract: The results of this study suggest that the cough trick can be an effective strategy for the reduction of pain for some children undergoing routine immunizations. However, additional research is needed to clarify the observed moderation by self-identified race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…It is stated in the literature that the basic potential mechanisms in the control of pain of the technique of coughing and blowing into a spirometer depend on the Valsalva manoeuvre, along with the method of directing the attention elsewhere (Kumar et al., ; Mohammadi et al., ; Suren et al., ; Usichenko et al., ; Wallace et al., ). The results of the present study showed that individuals in the coughing, spirometer and stress ball groups felt statistically less pain during the process of peripheral intravenous catheterisation than the individuals in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stated in the literature that the basic potential mechanisms in the control of pain of the technique of coughing and blowing into a spirometer depend on the Valsalva manoeuvre, along with the method of directing the attention elsewhere (Kumar et al., ; Mohammadi et al., ; Suren et al., ; Usichenko et al., ; Wallace et al., ). The results of the present study showed that individuals in the coughing, spirometer and stress ball groups felt statistically less pain during the process of peripheral intravenous catheterisation than the individuals in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Many such methods are in use to relieve pain during peripheral intravenous catheterisation, such as cold application (Ayg€ un et al, 2013), the use of the Buzzy device, which is in the shape of a bee and which applies cold via ice wings and vibration via a motor (S ßahiner, _ Inal, & Akbay, 2015), and diverting the attention (Canbulat, _ Inal, & S€ onmezer, 2014;Yoo, Kim, Hur, & Kim, 2011). Apart from these, studies have reported the use of the Valsalva manoeuvre to reduce interventional pain (Kumar, Budur, & Odappa, 2014;Mohammadi, Pajand, & Shoeibi, 2011;Wallace, Allen, Lacroix, & Pitner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There was no time to discuss in detail some other examples of afferent inputs that have been shown to ‘tune’ the cough center, although some are mentioned in the sections above. They include the external ear [101], the nasopharynx ([11,102,103] and see above), the heart [104], the abdominal viscera [105], the eye [106] and the skin ([79,8183,107], and see above). Nearly all the results described applied to the ‘classical’ cough reflex, starting with an inspiration and usually induced by capsaicin or citric acid aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…This applies for example to the skin [82–85,107], C-fiber receptors in the lungs [12,13,15], temperature and humidity in the respiratory tract [108,109], the pharynx [102,103], chest wall vibration [80,81,90,91], exercise [65,94] and the cerebral cortex (voluntary initiation and suppression of cough). An example of particular interest is the nose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation